An alternative view of the relationship between foreign direct investment inflows and economic growth in Central and Eastern European countries - Kusanović, Tino (Oeconomica Jadertina, 2021)
The paper analyses theoretically and empirically the  relationship between foreign direct investments and economic growth on a sample of Central and Eastern European countries. An unambiguous conclusion regarding the direction and intensity of the impact of two subject variables cannot be extrapolated from the available research on this relationship, questioning a priori the positive effects of FDI on the economic growth of the recipient country. The research highlighted that the potential effects of foreign savings on the economy of the recipient country depend both on its level of economic and institutional development and its growth model. Starting from the postulates of postKeynesian economic theory, the paper relies on the assumption that most countries in the research sample have adopted the demand led growth model. The research covers a sample of 15 Central and Eastern European countries for the period from 1995-2016. The empirical research was undertaken in two steps; in the first step, based on the results of Granger causality test, an increase in the GDP growth rate also led to an increase in total FDI inflows, while the opposite did not apply. In the second step, the undertaken panel data analysis tested the impact of economic growth and selected control variables on the total FDI inflow. In the conclusion, the empirical results are theoretically explained in the context of post-Keynesian economic theory based on the assumption that foreign savings (capital) in the case of low and middle-income countries mainly lead to an increase in personal consumption due to real exchange rate appreciation inducing an increase in current account deficit and creating (macro)economic imbalances.
Keywords: FDI; CEE countries; economic growth; real exchange rate; panel model